Effects of adding Fe2O3 and Fe3O4 nanoparticles to soil on germination and seedling characteristics of Oriental beech - Sevik, Hakan; Özel, Handan Ucun; Yıldız, Yafes; Özel, Halil Barış (BioResources, 2024)
Effects of Fe-based nanoparticles (Fe2O3 and Fe3O4) on germination parameters were studied for some seedling characteristics of Oriental beech (Fagus orientalis) seeds. Fe2O3 and Fe3O4 nanoparticle applications were made at concentrations of 400, 800, 1200, 1600, and 2000 mg/L on Fagus orientalis seeds collected from 10 different populations, and some germination and seedling characteristics were evaluated. Preliminary results generally indicated that low-dose nanoparticle applications positively affected germination and seedling characteristics, while increases in doses led to decreases in these parameters. Values obtained from high-dose nanoparticle applications were generally lower than those from the control group. The iron nanoparticles affected the parameters to different extents, Fe2O3 nanoparticles showed a significant positive effect on germination rate and radicle length, while exhibiting a significant negative effect on germination percentage and plumule length. The populations least affected by high-dose iron nanoparticle applications were Bursa Inegol, Karabuk-Yenice, and Ordu Akkus, while the most affected were the Bartin-Kumluca and Kahramanmaras-Andirin populations.
Keywords: O 4; nanoparticle; Germination; fe3o4; Fagus Orientalis; Nanoparticle; germination; fe2o3; O 3; fagus orientalis; TP248.13-248.65; Biotechnology